Nephrolepis exaltata - Hibiscus rosa-sinensis combination herbal mask decreases levels of reactive oxygen species in nasal wash - Prasetyo, Awal; Ariani, Resti; Antari, Arlita Leniseptaria; Sadhana, Udadi; Miranti, Ika Pawitra; Kristina, Tri Nur (Faculty of Medicine, Universitas Trisakti, 2020)
BackgroundPoor air and mask quality in the work environment increase the risks of inflammation, reactive oxygen species (ROS) production, ongoing oxidative stress, and superoxide dismutase 3 (SOD3) levels in the airways. The study aimed to investigate the effect of the Nephrolepis exaltata - Hibiscus rosa-sinensis (NE-HRS) combination herbal mask on the airways, as measured by ROS and SOD3 levels in the nasal wash of textile industry workers.MethodsThis was a pre- and post-test randomized controlled trial, consisting of 30 subjects with ³5-year working time, conducted for eight weeks and monitored every ten days. Subjects were randomized into 3 groups, regular surgical mask group (n=10), NE-HRS combination herbal mask group (n=10) and factory mask group (n=10). SOD3 and ROS levels were determined using ELISA. Data were analyzed with One-way ANOVA and multiple comparison tests.Results ROS levels decreased significantly in all groups (p=0.004). Regular surgical masks decreased ROS levels by 67.90 ± 50.66 pg/mL, NE-HRS combination herbal masks by 49.91 ± 45.06 pg/mL, and factory masks by 193.96 ± 128.36 pg/ml. SOD3 levels also decreased but not significantly (p=0.053). Differences in ROS levels between surgical mask and NE-HRS combination herbal mask was not significant (p=0.796). ConclusionHerbal masks laminated with NE-HRS combination significantly reduced ROS levels among textile industry workers. NE-HRS combination herbal masks have a similar protective effect to the regular surgical mask.